2021
DOI: 10.1111/sltb.12700
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging general risk surveillance to reduce suicide in early adolescents: Associations between suicidality, disordered eating, and other developmental risk factors

Abstract: Objective Suicide is a leading cause of death in early adolescents (i.e., children ages 11–14), underscoring the need for a more complex understanding of suicidality in youth. Syndemics framework posits that the overlap of multiple maladaptive behaviors (or risk factors) produces worse health outcomes compared to each behavior alone. The use of this framework in preventing suicide necessitates that identification of developmental risk factors that occur in tandem to suicide (e.g., disordered eating behaviors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…5 Early adolescence is a critical transitional period in human development involving major biological, emotional, cognitive, psychological and behavioural changes. 6 Thus, vulnerable adolescents are more prone to psychological and behavioural problems during this period. Suicide not only results in loss of life but also imposes substantial psychological burdens on the surviving family members and friends, such as prolonged grief, shock, anger, guilt, depression, anxiety and even suicidal thoughts, thereby contributing to a considerable financial toll on society.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…5 Early adolescence is a critical transitional period in human development involving major biological, emotional, cognitive, psychological and behavioural changes. 6 Thus, vulnerable adolescents are more prone to psychological and behavioural problems during this period. Suicide not only results in loss of life but also imposes substantial psychological burdens on the surviving family members and friends, such as prolonged grief, shock, anger, guilt, depression, anxiety and even suicidal thoughts, thereby contributing to a considerable financial toll on society.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…54 Although there are fewer studies about suicidality and body dissatisfaction for middle schoolers, 1 study using the YRBS for Kentucky middle school students found that those with both disordered eating behaviors and suicidality were more likely to engage in a number of risk behaviors including cigarette, alcohol, and prescription drug use. 55 Finally, a study using the YRBS for North Carolina middle school students found that females who perceived themselves as overweight were more likely to report suicidal thoughts and actions. 56 As demonstrated by the studies above, research documenting the relationship between body image and risk behaviors, especially for females, uses a variety of measures, with older adolescents more often being the focus rather than early adolescents.…”
Section: Suicidal Ideation and Body Dissatisfactionmentioning
confidence: 99%
“…A third study also using national YRBS high school data found that body image and weight control behaviors, among other factors, were significant predictors of suicidal behaviors 54 . Although there are fewer studies about suicidality and body dissatisfaction for middle schoolers, 1 study using the YRBS for Kentucky middle school students found that those with both disordered eating behaviors and suicidality were more likely to engage in a number of risk behaviors including cigarette, alcohol, and prescription drug use 55 . Finally, a study using the YRBS for North Carolina middle school students found that females who perceived themselves as overweight were more likely to report suicidal thoughts and actions 56 …”
Section: Substance Use and Body Dissatisfactionmentioning
confidence: 99%